Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 55. Beitrag. Lepidoptera: Cossidae. - Daniel, Franz jun.; Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The material of the expedition to Albania by Deutsches Entomologisches Institut contains only 3 Cossidae of 2 species, but one of these species (Dyspessa salicicola Eversmann) is new in the fauna of Albania. The data of the finds of Cossidae made in Albania are compiled, and a survey is given of the distribution of this family in the Balkan peninsula. Of the 8 species found in the Balkan region, 6 species are known from Albania.